How Covid-19 changed the epidemiology of febrile urinary tract infections in children in the emergency department during the first outbreak - Laura Cesca; Ester Conversano; Federica Alessandra Vianello; Laura Martelli; Chiara Gualeni; Francesca Bassani; Milena Brugnara; Giulia Rubin; Mattia Parolin; Mauro Anselmi; Mara Marchiori; Gianluca Vergine; et al. (BMC, 2022)
Abstract Background The first Covid-19 pandemic affected the epidemiology of several diseases. A general reduction in the emergency department (ED) accesses was observed during this period, both in adult and pediatric contexts. Methods This retrospective study was conducted on the behalf of the Italian Society of Pediatric Nephrology (SINePe) in 17 Italian pediatric EDs in March and April 2020, comparing them with data from the same periods in 2018 and 2019. The total number of pediatric (age 0-18 years) ED visits, the number of febrile urinary tract infection (UTI) diagnoses, and clinical and laboratory parameters were retrospectively collected. Results The total number of febrile UTI diagnoses was 339 (73 in 2020, 140 in 2019, and 126 in 2018). During the first Covid-19 pandemic, the total number of ED visits decreased by 75.1%, the total number of febrile UTI diagnoses by 45.1%, with an increase in the UTI diagnosis rate (+ 121.7%). The data collected revealed an increased rate of patients with two or more days of fever before admission (p = 0.02), a significant increase in hospitalization rate (+ 17.5%, p = 0.008) and also in values of C reactive protein (CRP) (p = 0.006). In 2020, intravenous antibiotics use was significantly higher than in 2018 and 2019 (+ 15%, p = 0.025). Urine cultures showed higher Pseudomonas aeruginosa and Enterococcus faecalis percentages and lower rates of Escherichia coli (p = 0.02). Conclusions The first wave of the Covid-19 pandemic had an essential impact on managing febrile UTIs in the ED, causing an absolute reduction of cases referring to the ED but with higher clinical severity. Children with febrile UTI were more severely ill than the previous two years, probably due to delayed access caused by the fear of potential hospital-acquired Sars-Cov-2 infection. The possible increase in consequent kidney scarring in this population should be considered.